2010
DOI: 10.1021/cm902635j
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Friendly Method To Produce Graphene That Employs Vitamin C and Amino Acid

Abstract: Graphene sheets are of significance in fundamental and applied science for their exceptional electronic, mechanical, and thermal properties. Among the different methods for producing graphene sheets, chemical reduction is favorable, because it can be scalable in production and versatile in realizing abundant chemical functionalization. Here, we report an environment-friendly method to produce graphene that employs Vitamin C as the reductant and amino acid as the stabilizer. This study is the first example of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
417
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 726 publications
(457 citation statements)
references
References 51 publications
30
417
1
Order By: Relevance
“…hydrazine [38] and hydroxylamine hydrochloride [13]. Previous studies have suggested possible mechanisms for the effects of sulfur-containing compounds [8,9,15]. We confirmed that the products contained SO 4 2-using the BaCl 2 method that indicates a positive based on a white precipitate, with findings consistent with those of Chen et al [8].…”
Section: Graphene Oxide and Reductantssupporting
confidence: 89%
See 2 more Smart Citations
“…hydrazine [38] and hydroxylamine hydrochloride [13]. Previous studies have suggested possible mechanisms for the effects of sulfur-containing compounds [8,9,15]. We confirmed that the products contained SO 4 2-using the BaCl 2 method that indicates a positive based on a white precipitate, with findings consistent with those of Chen et al [8].…”
Section: Graphene Oxide and Reductantssupporting
confidence: 89%
“…L-ascorbic acid, also known as Vitamin C [9], sodium borohydride [37], and sodium hydrosulfite [15] were selected as candidates because of reducing effects comparable to hydrazine [38]. Figure 2 shows the results of simple tests of these reductants at room temperature.…”
Section: Graphene Oxide and Reductantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 284.5 eV for the C 1s spectra represents non-oxygenated C-C bonding, which is intensified after reduction. The broad peak at 288.4 eV can be assigned to the carbon-oxygen bonding, including C-O and C=O 42 . This peak is significantly weakened upon reduction.…”
Section: Characterizations Of Cathode Materialsmentioning
confidence: 99%
“…Recently, new and more eco-friendly reducing agents for GO have been reported for the substitution of hydrazine, such as ascorbic acid (vitamin C) (66)(67)(68), alkyl amines (69)(70)(71)(72), reducing sugars (43,73), wild carrot root (74), metal nanoparticles (75,76) and powders (77,78), phytoextracts (79), green tea (80), baker's yeast (81), supercritical alcohols (82) and amino acids (67,83).…”
Section: Introductionmentioning
confidence: 99%